Organizational Health Literacy as a Tool for Health Equity: Application in a High-Risk Infant Follow-Up Program - Lindsay E. Rosenfeld; Kelly McCullagh; Carolyn J. King; Micaela Torres; Jonathan S. Litt (MDPI AG, 2023)
Background: Healthy People 2030 emphasizes personal health literacy (individual skills) and organizational health literacy-the degree to which organizations equitably enable individuals to find, understand, and use information and services to inform health-related decisions and actions for themselves and others. However, research on the latter is in the early stages. Methods: This study describes an organizational health literacy assessment in a U.S. urban academic children's hospital. A variety of evidence-based health literacy assessments were used to assess patient information materials and the environment, including institutional practices, navigation, culture and language, and communication. Trained interviewers and analysts reached consensus for all assessments. Results: Information Items: SMOG scores (n = 9) ranged from 7th- to 14th-grade reading level (average = 11.3). PEMAT-P scores (n = 9) ranged from 43.8% to 93.8% understandability and 0% to 80% actionability. CDC CCI scores (literacy demand) (n = 6) ranged from 18.2% to 58.8% (≥90% = excellent). SAM scores (suitability) (n = 6) fell in the "adequate" range (43.2-58.3%). The PMOSE/IKIRSCH scores (complexity) (n = 3) noted low-moderate difficulty. Apter's Hierarchy (n = 4) revealed three numeracy domains (50% = descriptive purposes and decision-making, 100% = interpreting information). Organization-level: Walking interviews highlighted organizational facilitators and barriers related to the pre-visit and visit environments. HLE2 domain scores ranged from 52% to 68%. Conclusions: Organizational health literacy demands far outweigh the average literacy skills of adults in the U.S. (patients and staff). Findings can be used to hone quality improvement and other processes to focus on structural solutions to increase health equity.